Distinct Siderophores Contribute to Iron Cycling in the Mesopelagic at Station ALOHA - Bundy, Randelle M.; Boiteau, Rene M.; McLean, Craig; Turk-Kubo, Kendra A.; McIlvin, Matt R.; Saito, Mak A.; Van Mooy, Benjamin A. S.; Repeta, Daniel J. (Frontiers in Marine Science, 2018)
The distribution of dissolved iron (Fe), total organic Fe-binding ligands, and siderophores were measured between the surface and 400 m at Station ALOHA, a long term ecological study site in the North Pacific Subtropical Gyre. Dissolved Fe concentrations were low throughout the water column and strong organic Fe-binding ligands exceeded dissolved Fe at all depths; varying from 0.9 nmol L-1 in the surface to 1.6 nmol L-1 below 150 m. Although Fe does not appear to limit microbial production, we nevertheless found siderophores at nearly all depths, indicating some populations of microbes were responding to Fe stress. Ferrioxamine siderophores were most abundant in the upper water column, with concentrations between 0.1-2 pmol L-1, while a suite of amphibactins were found below 200 m with concentrations between 0.8-11 pmol L-1. The distinct vertical distribution of ferrioxamines and amphibactins may indicate disparate strategies for acquiring Fe from dust in the upper water column and recycled organic matter in the lower water column. Amphibactins were found to have conditional stability constants (log ) ranging from 12.0-12.5, while ferrioxamines had much stronger conditional stability constants ranging from 14.0-14.4, within the range of observed L1 ligands by voltammetry. We used our data to calculate equilibrium Fe speciation at Station ALOHA to compare the relative concentration of inorganic and siderophore complexed Fe. The results indicate that the concentration of Fe bound to siderophores was up to two orders of magnitude higher than inorganic Fe, suggesting that even if less bioavailable, siderophores were nevertheless a viable pathway for Fe acquisition by microbes at our study site. Finally, we observed rapid production of ferrioxamine E by particle-associated bacteria during incubation of freshly collected sinking organic matter. Fe-limitation may therefore be a factor in regulating carbon metabolism and nutrient regeneration in the mesopelagic.